Kontribusi Imperium Usmani, Moghal, dan Safawi dalam Pembentukan Peradaban Islam pada Zaman Pertengahan - Alifah, Nurul; Erman, Erman (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This research examines the contribution of the Ottoman Turkish Empire, the Moghal Empire in India and the Safavid Empire in Persia to the formation and development of Islamic civilisation in medieval times. Using a historical and qualitative approach, the study analyses the influence of the three great powers in political, economic, scientific and cultural aspects. The findings show that the Ottoman Turks played an important role in administration and architecture, the Moghals contributed to cultural integration and monumental artistic achievements, while the Safavids strengthened Shia identity and supported the development of Persian art. The interaction between these three empires not only enriched the heritage of Islamic civilisation but also fostered mutually supportive scientific and economic progress. This research provides a comprehensive overview of how the contributions of each empire formed an influential network of civilisations and made an impact that endures to this day.